2007
DOI: 10.2174/156720507780362065
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Adiposity and Dementia

Abstract: Adipose tissue is the largest endocrine gland in the body, yet only recently has its role in neurodegenerative disease been considered. Prospective population level evidence has emerged to show that both obesity and overweight, is associated with an increased risk of all cause dementia, Alzheimer's disease (AD), and underlying neurodegenerative changes. Weight loss in late life however is associated with dementia, and those categorized as underweight are also at a greater risk of dementia. Given the current ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 65 publications
0
56
1
5
Order By: Relevance
“…First, higher BMI is associated with diabetes and vascular diseases, which are related to dementia risk. 12 Nonetheless, in our study, the association between midlife high BMI and dementia remained significant after controlling for lifespan vascular diseases, suggesting that nonvascular pathways might play an important role in the adiposity-dementia association. Second, higher adiposity at midlife may reflect a lifetime exposure to an altered metabolic and inflammatory state.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…First, higher BMI is associated with diabetes and vascular diseases, which are related to dementia risk. 12 Nonetheless, in our study, the association between midlife high BMI and dementia remained significant after controlling for lifespan vascular diseases, suggesting that nonvascular pathways might play an important role in the adiposity-dementia association. Second, higher adiposity at midlife may reflect a lifetime exposure to an altered metabolic and inflammatory state.…”
Section: Discussioncontrasting
confidence: 65%
“…3,5,7,9 Currently, the prevalence of overweight and obesity is over 50% among adults in the United States and Europe. 11 Although adiposity may be linked to dementia through several biologically plausible pathways, 12 our understanding of the mechanisms for such an association is still limited. Both obesity and dementia are complex genetic and lifestyle-related disorders.…”
mentioning
confidence: 99%
“…In contrast to late-life diabetes, mid-life diabetes was associated with an increased risk of dementia even when controlling for genetic and familial factors, suggesting that mid-life diabetes-dementia association might be exogenous and is more likely attributable to adulthood environ- Obesity is related to inflammation and insulin resistance, and the lifespan-dependent relation of obesity with dementia has been reported (46). In our study, information on weight and height were based on self-or informant report, and BMI as a covariate in the analyses may lead to residual confounding.…”
Section: Discussionmentioning
confidence: 96%
“…Two other well-designed and powerful studies found similar results (Kalmijn et al 2000;Rosengreen et al 2005). More recently a 36-year longitudinal study of a large cohort (n = 10,136) found that people who were obese at midlife (BMI Ͼ 30) had a 3.10-fold increased risk of AD (HR = 3.10; 95% CI = 2.19-4.38) and a 5-fold increased in risk of Vad (HR = 5.01; 95% CI = 2.98-8.43), while those who were overweight (BMI Ͼ 25) had a 2-fold increased risk of AD and Vad (HR = 2.09; 95% CI = 1.69-2.60 for Alzheimer disease and HR = 1.95; 95% CI = 1.29-2.96 for vascular dementia), independent of vascular comorbidities (Whitmer 2007). All these results suggest that an increased BMI is likely to be an important risk factor for dementia, even though there are no published reports that take into account the role of ApoE ε4.…”
Section: Adiposity Metabolic Syndrome and Cognitive Declinementioning
confidence: 99%